Oil and the Eruption of the Algerian Civil War: A Context-sensitive Analysis of the Ambivalent Impact of Resource Abundance - Miriam Shabafrouz (German Institute of Global and Area Studies (GIGA), 2010)
Algeria's intrastate war in the 1990s, during which militant Islamists and the state fought fiercely against each other, still raises questions concerning the decisive factors leading to its onset and escalation. This paper uses the resource curse approach and the rentier state theory to understand the impact resource wealth could have had on the outbreak of this violent conflict, then goes one step further, adopting a context-sensitive approach. This approach attempts to juxtapose those conditions directly linked to the resource sector with the general conflict-fueling conditions diagnosed in Algeria. It takes into account conditions both within the country and in the international context. The application of a context matrix allows us to examine the interplay of resource-related factors and other conflictdriving forces, such as socioeconomic, demographic and ideological changes. Such an approach not only broadens the general understanding of the resource-violence link but also enhances our understanding of the eruption of violence in Algeria. – – Erdöl und der Ausbruch des algerischen Bürgerkriegs: Eine kontextsensible Analyse der ambivalenten Auswirkungen von Ressourcenreichtum. Der innerstaatliche Krieg in Algerien, in dem militante Islamisten und die staatlichen Sicherheitskräfte über acht Jahre lang gegeneinander kämpften, lässt Fragen offen hinsichtlich der entscheidenden Faktoren, die zu seinem Ausbruch und seiner Eskalation führten. Um den Einfluss des Ressourcenreichtums auf den Beginn dieses Krieges zu verstehen, verwendet der vorliegende Artikel den Ressourcenfluch-Ansatz und die Rentierstaatstheorie, geht jedoch mit einer kontextsensiblen Analyse noch einen Schritt weiter. Mit einer Kontext-Matrix kann das Zusammenspiel von ressourcenbezogenen Faktoren mit anderen Konflikt treibenden Kräften, wie sozioökonomischen, demografischen und ideologischen Veränderungen, systematisch untersucht werden. Dabei werden direkt mit dem Ressourcensektor verknüpfte Bedingungen von solchen unterschieden, die als allgemeine Konflikt fördernde Bedingungen in Algerien diagnostiziert werden können, und dies nicht nur innerhalb des Landes sondern auch mit Blick auf sein internationales Umfeld. Damit trägt die vorliegende Analyse zu einem differenzierteren Verständnis der multiplen Ursachen des Gewaltausbruchs in Algerien bei.
Keywords: 300; Algeria; oil; civil war; resource curse; rentier state theory; context approach; Bürgerkrieg; Erdölvorkommen; Rent Seeking; Algerien